ANALISIS STUDI KASUS KRISIS KETERSEDIAN AIR MUSIM KEMARAU DALAM UPAYA MENANGGULANGI PADA MASYARAKAT DESA BUTUH - . Sudarti; Nila Rayi Puspitasari (EKOLOGIA, 2021)
Water is a source of life that must exist in human life. Water supply crises have hit a lot due to drought disasters from the dry season. Drought is a disaster that occurs slowly due to changes in weather patterns that last a long time. A village that is located in Kediri Regency, namely Butuh Village has experienced a drought. Efforts that must be made can help reduce the impact of extreme climate change disasters. So, this article is used to add insight into the efforts and solutions that can be implemented. Respondents in the study were sixteen respondents with ten respondents who experienced the dry season, five people came to each house for observation. The results of the analysis that the author conducted through interviews resulted in a process carried out by the community by drilling wells and five people using bucket wells. However, if the drilling of wells by means of continuous deepening of the ground hole can have a dangerous impact on the environment. So, the authors provide another solution by making biopores in each house.